Features of Training a Modern Fashion Business Manager - Bryl, Maryna; Sabadin, Oleksandr (Socio-Cultural Management Journal, 2023)
Introduction. The relevance of the study is due to the fact that by integrating into the international educational space, the field of fashion education in Ukraine can comprehend foreign and domestic educational practices, creating modern management training programmes for such a branch of the creative industries as fashion, namely fashion business managers. Purpose and methods. The purpose of the article is a theoretical analysis of the peculiarities of training modern fashion business managers in the system of higher education in Ukraine and abroad. The methodological basis of the study is the methods of studying experience and analysis of primary sources and documentation in the field of education, pedagogical modelling. Results. The paper analyses the peculiarities of training fashion business managers in the higher education system in Ukraine, in particular, the content of educational programmes and professional growth trajectories, and identifies effective ways to update them based on the experience of specialised fashion and design universities from other countries. It is proved that the training of modern fashion business managers is a flexible, open system aimed at forming a synthesis of individual qualities required by a modern specialist to perform his/her professional functions. Conclusions. The scientific novelty lies in the attempt to present an analysis of various educational programmes for the training of fashion business managers in Ukraine, to compare the content of such programmes with approaches to the development of educational programmes in different countries. The practical significance of the results is to understand the existing approaches to the training of fashion business managers in Ukraine in order to modernise and flexibly develop educational programmes in universities.